2014
DOI: 10.1007/978-1-4939-2309-0_27
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Analysis of Membrane Transport in Yeast Using Invertase Reporters

Abstract: Transport of membrane proteins between cellular organelles requires the concerted action of many regulatory factors, which aid in cargo recognition and vesicle formation, targeting, and fusion. The yeast Saccharomyces cerevisiae is a useful model system for studying such regulators, due to the availability of genome-wide mutant collections and reporter proteins that provide sensitive biochemical readouts of individual transport pathways. Here, we describe an enzymatic invertase assay for evaluating endocytic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…The colorimetric liquid invertase assay used here is based on the assays described by Darsow et al and Dalton et al First, overnight cultures grown in synthetic selective media with 2% fructose were diluted to 1 OD 600 or 10 OD 600 /mL depending on the expected level of secretion. A total of 20 μL of the stocks were added to 30 μL of 0.1 M sodium acetate.…”
Section: Methodsmentioning
confidence: 99%
“…The colorimetric liquid invertase assay used here is based on the assays described by Darsow et al and Dalton et al First, overnight cultures grown in synthetic selective media with 2% fructose were diluted to 1 OD 600 or 10 OD 600 /mL depending on the expected level of secretion. A total of 20 μL of the stocks were added to 30 μL of 0.1 M sodium acetate.…”
Section: Methodsmentioning
confidence: 99%
“…The identification of Apm2, but not the more abundant μ-subunit isoform Apm1, was unexpected and suggested that Apm2-containing AP-1R complex has a specific role in Snc1 sorting. To confirm these observations, we used a quantitative assay that measures the invertase (Suc2) activity of GSS present at the cell surface ( Figure 1A ; Dalton et al. , 2015 ).…”
Section: Resultsmentioning
confidence: 98%
“…Strains expressing the GSS construct were grown for 20 h in 2 ml of YP-fructose (final OD 600 of ∼10). Cultures were diluted to 3 OD 600 /ml, and the liquid invertase assay was performed as described ( Dalton et al. , 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…resulting reporter, GSS (here called GSI; Figure 1A) was used to assay the integrated levels of endocytosis and exocytosis in high-throughput screens of yeast gene deletion mutants. [16][17][18] The v/R-SNARE protein Nyv1 is normally targeted to the limiting membrane of the yeast vacuole through the AP-3 pathway. 19,20 Nyv1 sorting requires interaction between a YXXΦ-like motif (YGTI) in Nyv1's N-terminal longin domain and Apm3, the AP-3 μ-chain.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, these results indicate that GNSI is suitable for large-scale screening using automated mating and sporulation procedures. 17,26 Finally, we asked if GNSI could be used in growth selections. Mutants lacking extracellular invertase exhibit growth defects when sucrose rather than dextrose is the primary carbon source.…”
Section: Resultsmentioning
confidence: 99%